The metastasis landscape of Clonorchis sinensis-associated hepatocellular carcinoma: an integrated multi-omics and clinical study - Zhou, Lingling; Sun, Lin; Huang, Xuhang; Chen, Junxian; Huang, Taijun; Xu, Yulong; Luo, Xiaorong; Wei, Caibiao; Liu, Fengfei; Pan, Xiaolan; Dong, Madanni; Su, Jingyu; et al. (Frontiers in Immunology, 2026)
BackgroundHepatocellular carcinoma (HCC) patients with Clonorchis sinensis (Cs) infection tend to exhibit a poorer prognosis compared to those without infection. Nevertheless, the molecular mechanisms underlying Cs-associated HCC, particularly those linked to metastatic progression, remain poorly understood. This study therefore seeks to elucidate the role of C. sinensis infection in promoting metastasis.MethodsThrough a clinical retrospective analysis, we compared overall survival and metastasis incidence between HCC patients with and without Cs infection. To explore the underlying mechanisms, we conducted integrated multi-omics analyses—including RNA-seq, miRNA-seq, ATAC-seq, WGBS-seq, oxWGBS-seq, and ChIP-seq—to profile 369 metastasis-related genes in Cs+ and Cs- HCC tumors. The expression of three key metastasis-related genes was further validated by RT–qPCR, and Transwell and wound-healing assays were performed in vitro to confirm the pro-metastatic effect of Cs infection on HCC cells.ResultsIn HCC patients, Cs infection was associated with poorer overall survival and an increased metastasis rate. We identified 20 metastasis-related genes, with SPP1, MMP2, and VCAM1 as central hubs, together with 41 interacting miRNAs and 71 accessible promoter regions. Histone modifications—particularly H3K9ac, H3K27ac and H3K4me3—were correlated with chromatin accessibility in the promoters of these genes. Molecular experiments further demonstrated that Cs infection enhances the metastatic potential of HCC.ConclusionsOur study reveals that Cs infection promotes HCC metastasis through gene and epigenetic alterations, providing mechanistic insights and identifying potential targets for early intervention.